THE IMPACT OF IN VIVO ADMINISTRATION OF A SYNTHESIS PRODUCT (BY-PRODUCT OF SALICYLIC ACID) ON SOME BIOCHEMICAL PARAMETERS ON RATS - LETITIA STANA; ALEXANDRA TRIF; F. MUSELIN; ALFA XENIA LUPEA; MIRABELA PADURE (Scientific Papers Animal Science and Biotechnologies, 2023)
The goal of this study is to establish the in vivo impact of a by-product of salicylic acid, 5-cloro-2-hidroxy-azotyl-sulfamoil-phenyl benzamyde synthesis product (5ClSA-SA), synthesized at the Technical University, Faculty of Industrial Chemistry of Timisoara, on some parameters of energetic metabolism. The experimental results shows that the synthesis product has induced a strong significant increase (p<0.01) of glycemia compared to tests, in direct relation with administration period and a fluctuation of cholesterol values with decrease followed by strong significant increase (p<0.01) compared to tests. Glycemia and plasmatic cholesterol values were situated between physiological limits. Triglycerides registered strong significant increases (p<0.01) in direct relation with administration period, over the physiological limits.